Magnetoresistance behavior in electroplated and sputtered Bi thin films - Jeun, M. H.; Lee, K. I.; Lee, K. H.; Kim, D. Y.; Chang, J. Y.; Shin, K. H.; Han, S. H.; Ha, J. G.; Lee, W. Y. (ELSEVIER SCIENCE BV, 2004)
The magnetotransport properties of the electroplated and sputtered Bi thin films have been investigated in the range 4 - 300 K. Both the films are found to exhibit very large MR, similar to 600%, at room temperature. The room temperature MR in the sputtered films depends on the grain size, in contrast to the electroplated films. (C) 2003 Elsevier B. V. All rights reserved.